(untitled) (Physical Education, Health and Social Sciences, 2026)
Agriculture extension agent serves as the vital link between research and the farming community. This study assessed the effectiveness of extension services and identified production constraints in District Abbottabad, Pakistan. Data were collected from 112 farmers across four villages and analysed using SPSS. The demographic attributes revealed that majority of the respondents were literate (69%) and (43%) were from age group of 51 and above. About (33%) of the respondents were landholding size “5.1 acres and above” and had good farming experience of “21years and above” (84%). Paired sample t-tests revealed highly significant improvements (P < 0.01) following the extension interventions, where scientific recommendations reduced seed rates for wheat (from 64.08 to 50 kg/acre) and maize (8.09 to 6.63 kg/acre) while simultaneously increasing respective yields by 285.94 kg/acre and 178.78 kg/acre". Chi-square analysis confirmed that literacy levels significantly influenced (p < 0.01) farmers’ knowledge of extension services. Programs like field days and demonstrations successfully disseminated technology. The study identified key challenges, including poor financial conditions, water scarcity and less number of extension workers. The study recommends that policymakers should prioritize the strengthening of agricultural extension services in District Abbottabad, along with that, government may take into account the provision of advanced trainings to the farmers. Furthermore the study suggested that farming communities should be actively involved in the planning and implementation of agricultural extension services.